Loading [MathJax]/jax/output/CommonHTML/jax.js

Supplement to Frege's Theorem and Foundations for Arithmetic

First Derivation of the Contradiction

[Note: We use ϵF to denote the extension of the concept F. We use the expression ‘F(ϵG)’ to more clearly express the fact that the extension of the concept G falls under F.]

The λ-expression which denotes the concept being the extension of a concept one doesn’t fall under is

[λxF(x=ϵF&¬Fx)]

As we saw in the text, we know that such a concept as this exists, by the Comprehension Principle for Concepts. Let ‘P’ abbreviate this name of the concept. So ϵP exists, by the Existence of Extensions principle.

Now suppose that P(ϵP), i.e., suppose

[λxF(x=ϵF&¬Fx)](ϵP)

Then, by the principle of λ-Conversion, it follows that

F[ϵP=ϵF&¬F(ϵP)]

Let H be an arbitrary such concept. So we know the following about H

ϵP=ϵH&¬H(ϵP)

Now given Law V, it follows from the first conjunct that x(PxHx). So since ¬H(ϵP), it follows that ¬P(ϵP), contrary to hypothesis.

So suppose instead that ¬P(ϵP). But, now, by λ-conversion, it follows that:

¬F[ϵP=ϵF&¬F(ϵP)],

i.e.,

F[ϵP=ϵFF(ϵP)]

But by instantiating this universal claim to P, it follows from the self-identity of ϵP that P(ϵP), contrary to hypothesis.

Contradiction.

Copyright © 2018 by
Edward N. Zalta <zalta@stanford.edu>

This is a file in the archives of the Stanford Encyclopedia of Philosophy.
Please note that some links may no longer be functional.
[an error occurred while processing the directive]